ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI AUDITOR UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING (Studi Empiris pada Kantor Akuntan Publik di Semarang) - Destriana Kurnia Kreshastuti; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This study aims to obtain empirical evidence of factors that affect auditor to make whistleblowing intention. This study refers to Curtis and Taylor (2010) by using the concept of the Theory of Planned Behavior (TPB) as a theoritical basis. This study uses primary data to obtained important information from the respondents by using convinience sampling method. Respondents in this study were 55 auditors who worked in public accounting firm in Semarang City, Indonesia. Statistical analysis method used is multiple linear regression. Hypothesis testing is done with the help of software IBM SPSS Statistics 19. The result of this study indicates: (1) Professional Identity positively significant influence whistleblowing intention; (2) Auditor who have higher organizational commitment that auditors who have a commitment to co-workers has not significant influence whistleblowing intention; (3) Moral intensity positively significant influence whistleblowing intention; (4) Auditor's personal characteristics is consisted of Gender, Age, Education, Experience (based on years experience) and Level Position at firm has not significant influence whistleblowing intention.